2018
DOI: 10.1016/j.ejvs.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine Aortic Arch Variant in Patients with Aortic Dissection and its Implications in the Outcome of Patients with Acute Type B Aortic Dissection

Abstract: The BA should be considered as a predictor of the outcome for patients with type B aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…Although seven types of AA have been described previously, only four types were found in the study population [7]; Type 4, 5 and 7 arches were not reported in the study group. The current study agrees with many previous studies by reporting Type 2 AA as the most prevalent arch variant [4,7,8,12,14,15,[19][20][21]. However, Qiu et al (n = 120) in a cadaveric study have reported type 3 AA (left vertebral artery directly arising from the AA; 7.5%) as the most prevalent anomaly [11].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although seven types of AA have been described previously, only four types were found in the study population [7]; Type 4, 5 and 7 arches were not reported in the study group. The current study agrees with many previous studies by reporting Type 2 AA as the most prevalent arch variant [4,7,8,12,14,15,[19][20][21]. However, Qiu et al (n = 120) in a cadaveric study have reported type 3 AA (left vertebral artery directly arising from the AA; 7.5%) as the most prevalent anomaly [11].…”
Section: Discussionsupporting
confidence: 91%
“…As described earlier, type 2 AA was the most prevalent variant for many populations [7,[14][15][16][19][20][21].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This increase in the likelihood of thoracic aortic disease has been related to alterations in blood flow caused by the CILCA, generating areas of accelerated flow and heightened wall shear stress [9], which are linked to endothelial damage and arterial injury [10]. Furthermore, after dissection, patients with CILCA are more likely to undergo surgical aortic repair and present an increased risk of death [9,11]. As a consequence, an early identification of patients with CILCA may be beneficial as it could allow the implementation of tailored surveillance protocols in order to avert unexpected disease diagnoses and potential adverse events.…”
Section: Introductionmentioning
confidence: 99%